2017
DOI: 10.1159/000471881
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Vitamin D Levels in Relation to Risk of Overweight at 7 Years in the Danish D-Tect Case-Cohort Study

Abstract: Background: Vitamin D level in pregnancy may be associated with risk of overweight in the offspring later in life. Methods: In a case-cohort study based on Danish biobanks and registers we examined the association between 25-hydroxy-vitamin D (25(OH)D) level at birth and overweight at 7 years. Cases of overweight (n = 871) were randomly selected among 7-year-old children from the Copenhagen School Health Records Register (CSHRR) with a BMI above the 90th percentile. The cohort (n = 1,311) was a random sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…On the other hand, two recent cohort studies did not find any association between umbilical cord blood or maternal 25(OH)D concentrations and neonatal anthropometric measures such as birth weight and Ponderal Index ( 10 , 11 ) . Other studies have shown that vitamin D deficiency in pregnancy was associated with an increased risk of macrosomia and postnatal overweight ( 12 ) , as well as increased fat mass at ages 4 and 6 years ( 13 ) , whereas a recent study did not find any association between 25(OH)D concentration at birth and the risk of overweight at the age of 7 years ( 14 ) .…”
mentioning
confidence: 99%
“…On the other hand, two recent cohort studies did not find any association between umbilical cord blood or maternal 25(OH)D concentrations and neonatal anthropometric measures such as birth weight and Ponderal Index ( 10 , 11 ) . Other studies have shown that vitamin D deficiency in pregnancy was associated with an increased risk of macrosomia and postnatal overweight ( 12 ) , as well as increased fat mass at ages 4 and 6 years ( 13 ) , whereas a recent study did not find any association between 25(OH)D concentration at birth and the risk of overweight at the age of 7 years ( 14 ) .…”
mentioning
confidence: 99%
“…In addition to skeletal rickets, infants with vitamin D deficiency have risk for seizures and convulsions (tetany), delayed motor skills, hyperparathyroidism, underdeveloped musculature, anemia, and even cardiomyopathy or failure (see Pettifor et al, 2018). Longer term effects of infant deficiency in vitamin D include impaired immune functioning, persistent hyperparathyroidism, reduced kidney functioning, inhibited expression of vitamin D receptors (VDRs), and an increased risk of Types 1 and 2 diabetes, obesity, some cancers, neurological and behavioral disorders, cardiovascular diseases, or multiple sclerosis (Hollis and Wagner, 2017;Ideraabdullah et al, 2019;Jensen et al, 2017;Lucas et al, 2008;Pettifor et al, 2018;Reichetzeder et al, 2014). Some infants whose mothers were vitamin D deficient during pregnancy may not experience its impacts until well after birth.…”
Section: Englandmentioning
confidence: 99%
“…According to the numerous studies, nowadays the prevalence of vitamin D deficiency in different countries accounts for at least 50% [5]. Taking into consideration that human body produces vitamin D only when UV rays heat the skin, deficit conditions are prevalent especially in countries with few sunny days.…”
Section: Epidemiological Factors Of Vitamin D Deficiencymentioning
confidence: 99%